Hairy root transformation system as a tool for CRISPR/Cas9-directed genome editing in oilseed rape (Brassica napus) - Jedličková, Veronika; Mácová, Kateřina; Štefková, Marie; Butula, Jan; Staveníková, Jana; Sedláček, Marek; Robert, Hélène S. (Frontiers in Plant Science, 2022)
Our study examined the mutation efficiency of the CRISPR/Cas9 method for tryptophan aminotransferase BnaTAA1 genes involved in the auxin biosynthesis pathway. We made nine CRISPR/Cas9 constructs with various promoters driving the expression of a Cas9 from Staphylococcus aureus (SaCas9) or a plant codon-optimized Streptococcus pyogenes Cas9 (pcoCas9). We developed a fast and efficient system for evaluating the variety and frequency of mutations caused by each construct using Brassica napus hairy roots. We showed that pcoCas9 is more efficient in mutating the targeted loci than SaCas9 and the presence of the NLS signal enhanced the chance of mutagenesis by 25 %. The mutations were studied further in regenerated lines, and we determined the BnaTAA1 gene expression and heritability of the gene modifications in transgenic plants. Hairy root transformation combined with CRISPR/Cas9-mediated gene editing represents a fast and straightforward system for studying target gene function in the important oilseed crop Brassica napus.